Identification of Cytochrmoe oxidase p450 in Heptocytes generated from in vitro differentiation of mouse mesenchymal stem cells - Zedan, Zahraa K.; Hussain, Shalal M.; Salih, Shahlaa M. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
This study was designed to identify the presence of cytochrome oxidase p450 (CYP3A4), in the hepatic cell lines which was generated from the in vitro differentiation of mouse bone marrow mesenchymal stem cells. Bone marrow meenchymal stem cells were first isolated by collecting both the femur and tibia of the mouse thigh bone, then exess tissue were removed and the cells were flushed from the bones and cultured under highly aseptic conditions. The isolated cells were characterized as a mesenchymal stem cells via using immunocytochemistry analysis. The characterized hepatocytes were subjected to a differentiation protocol in which the differentiation medium was contained a spesfic growth factor including (Hepatocytes growth factor (HGF), Fibroblast growth factor4 (FGF4), Oncostatin M and Dexamethasone, All theses growth factor was used for directing the BM-MSCs twards the hepatic line of cells. After three weeks of the differentiation protocol the diffrentation cells were examined for the presence of Cytochrome oxidase p450 (CYP3A4), which consider as one of the specific markers of hepatocytes. Identification eas done via two different methods first, via using the immunocytochemical analysis for the antihuman mouse CYP3A4 antibody and second by ELIZA test. The results showed a posotive reactivity of the differentiated cells towards the mouse antihuman CYP3A4 antibody as well as the eliza results showed a significant increase in the enzyme level of the cell lysate during the weeks of the differentiation experiment.